Quantum dots and nanowires for photonics applications - Mokkapati, S; Joyce, H; Kim, Y; Gao, Q; Tan, H; Jagadish, C (2006)
We review our results on integrated photonic devices fabricated using InGaAs quantum-dots. Selective-area metal organic chemical vapor deposition (MOCVD) is used to grow the active region with quantum dots emitting at different wavelengths for fabrication of the integrated devices. We will also review the structural and optical properties of III-V nanowires, and axial and radial nanowire heterostructures grown by MOCVD. In addition to binary nanowires, such as GaAs, InAs, and InP, we have demonstrated ternary InGaAs and AlGaAs nanowires. Core-shell nanowires consisting of GaAs cores with AlGaAs shells, and core-multishell nanowires with several alternating shells of AlGaAs and GaAs, exhibit strong photoluminescence. Axial segments of InGaAs have been incorporated within GaAs nanowires to form GaAs/InGaAs nanowire superlattices.